2004
DOI: 10.1074/jbc.m403489200
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding Intermediate in the Peroxisomal Flavoprotein d-Amino Acid Oxidase

Abstract: The flavoenzyme D-amino acid oxidase (DAAO) from Rhodotorula gracilis is a peroxisomal enzyme and a prototypical member of the glutathione reductase family of flavoproteins. DAAO is a stable homodimer with a FAD molecule tightly bound to each 40-kDa subunit. In this work, the urea-induced unfolding of dimeric DAAO was compared with that of a monomeric form of the same protein, a deleted dimerization loop mutant. By using circular dichroism spectroscopy, protein and flavin fluorescence, 1,8-anilinonaphtalene su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…This indicates that re-establishing the proper protein-cofactor interaction during the refolding process was somewhat impaired. Noteworthy, the same results were also recently observed in the case of D-amino acid oxidase, a FAD-containing flavoprotein carrying a non-covalently bound flavin (24).…”
Section: Fig 3 Results Of Titration Of Wild-type (A) and H69a (B) Csupporting
confidence: 57%
See 1 more Smart Citation
“…This indicates that re-establishing the proper protein-cofactor interaction during the refolding process was somewhat impaired. Noteworthy, the same results were also recently observed in the case of D-amino acid oxidase, a FAD-containing flavoprotein carrying a non-covalently bound flavin (24).…”
Section: Fig 3 Results Of Titration Of Wild-type (A) and H69a (B) Csupporting
confidence: 57%
“…At first, both proteins were titrated with ANS in the presence of various urea concentrations, allowing determination of the change in fluorescence emission intensity at saturating ANS concentration (⌬F), the apparent K d for ANS binding, and the ratio between these two parameters (⌬F/K d ) (24). Values of the apparent K d for ANS binding to wild-type CO at increasing urea concentrations remained quite constant (135 Ϯ 20 M), whereas the parameter ⌬F/K d varied with the urea concentration, attaining a maximum at 4 M urea (Fig.…”
Section: Fig 1 Equilibrium Denaturation Curves Of Wild-type (Circlementioning
confidence: 99%
“…Although A300 is conserved in most enzymes, its replacement with Thr, as (34). However, after reactivation with cysteine and FAD, the variant recovered some activity, suggesting that the N302S variant may be in a partially folded and expanded dimeric state, like unfolding intermediates previously described for other flavoproteins (6,23). This partially unfolded form may partly recover the compact dimer structure after reactivation.…”
Section: Discussionmentioning
confidence: 72%
“…Surprisingly, it has been reported that DAAO can assemble properly in the cytosol and thus that the catabolic utilization of Damino acids is also active in the cytosol of C. boidinii [31] and H. polymorpha cells [32]. In contrast, we recently hypothesized that the folding intermediate identified for RgDAAO possesses the properties (e.g., it lacks the catalytic activity and the characteristic tertiary structure of the native enzyme but has a significant secondary structure and retains flavin binding) proposed for the inactive holoenzyme required for in vivo trafficking of DAAO through the peroxisomal membrane [50,51]. Biochemical properties of fungal DAAOs.…”
Section: Daaos From Fungimentioning
confidence: 90%